The Study Of Wear Process On Uncoated Carbide Cutting Tool In Machining Titanium Alloy - Sulaiman, Mohd Amri; Kasim, Mohd Shahir (2012)
The uncoated carbide cutting tools were used in turning titanium alloy Ti6Al4V bar with hardness of 340HV. The main objective to find the wear behaviour of the cutting tool based on the flank wear data. The experiments were performed under dry cutting condition at various combinations of cutting speed and feed rate. The cutting speeds selected in the experiment were 15, 25, 35 and 45 m/min. Meanwhile the feed rates were used at 0.02 and 0.04 mm/rev. In this research depth of cut, doc was kept constant at 0.5 mm for all combinations of cutting parameters. Tool wear was measured under optical microscope and the data of flank wear which was gained through the experiment has been analysed. According to these graph shown that the affected of cutting parameters onto tool wear. The experiment’s result showed that the flank wear increased with the cutting speed and feed rate. The flank wear occurs gradually at beginning of machining and at the end of failure when Vbavg reached 0.3 mm where flank wear occurs.